KEPUASAN KERJA SEBAGAI PEMEDIASI PENGARUH TINDAKAN SUPERVISI DAN KOMITMEN ORGANISASI PADA KINERJA AUDITOR - Kartika Sari, Ni Wayan Diah; Dwirandra, Anak Agung Ngurah Bagus (E-Jurnal Akuntansi; Vol 15 No 2 (2016), 2016)
The purpose of this study was to determine the effect of supervision measures and organizational commitment in the performance of the auditor in public accounting firm either directly or indirectly through job satisfaction. This research was conducted at the Public Accounting Firm (KAP) in the city of Denpasar. The sampling technique used was purposive sampling. Methods of data collection using questionnaires with respondents as many as 40. The analysis technique using path analysi. The conclusion of this study is able to mediate the effect of job satisfaction on the performance of supervisory action, while job satisfaction is not able to mediate the effect of commitment on the performance of auditors as path error occurs. Actions that further enhanced supervision and change the direction of the relationship into job satisfaction toward the organization's commitment to the performance of auditors.
Keywords: Supervision Measures, Organizational Commitment, Job Satisfaction, Performance